2011
DOI: 10.1159/000321219
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations in Diabetic Patients Attending a Diabetic Clinic in the Qassim Region, Saudi Arabia

Abstract: prevalence of skin manifestations in type 2 than type 1, and as the duration of diabetes increased, the likelihood of developing skin manifestations also increased. Early referral to the dermatologist may help to detect complications of the skin in diabetes at an early stage and may prevent disability caused by these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
0
16
0
4
Order By: Relevance
“…According to a study from Saudi Arabia, for those patients having diabetes of less than 5 years' duration, the incidence of skin manifestations was 80.6%; for those having diabetes for more than 5 years, the incidence was 98%.This difference was statistically significant (P<0.001). 21 Study by Sanad et al showed that the number of patients suffering from skin manifestations increased with a longer duration of DM, but there was no statistically significant relation between skin manifestations of DM and the duration of DM, except for diabetic bullae (P=0.04), diabetic dermopathy (P=0.003), and tinea pedis (P=0.001), which were significantly present in DM of more than 5 years' duration. The prevalence of skin manifestations was higher as the duration of diabetes increased.…”
Section: Discussionmentioning
confidence: 95%
“…According to a study from Saudi Arabia, for those patients having diabetes of less than 5 years' duration, the incidence of skin manifestations was 80.6%; for those having diabetes for more than 5 years, the incidence was 98%.This difference was statistically significant (P<0.001). 21 Study by Sanad et al showed that the number of patients suffering from skin manifestations increased with a longer duration of DM, but there was no statistically significant relation between skin manifestations of DM and the duration of DM, except for diabetic bullae (P=0.04), diabetic dermopathy (P=0.003), and tinea pedis (P=0.001), which were significantly present in DM of more than 5 years' duration. The prevalence of skin manifestations was higher as the duration of diabetes increased.…”
Section: Discussionmentioning
confidence: 95%
“…10,13 Large, recent series of patients attending diabetes clinics identified GA in 0-1.8% and NL in 0-1.4% of patients respectively. [14][15][16][17] REVIEW Traditionally, it has been thought that glycaemic control has no effect on the course of NL, however Cohen et al challenged this view following reappraisal of the original data and argued that tighter glycaemic control may prevent or ameliorate the condition. 18 Furthermore, they suggest the possibility that NL may be a separate condition in people with and without diabetes.…”
Section: Association With Diabetesmentioning
confidence: 99%
“…8.3%of patients with cutaneous manifestations had Seborrheic dermatitis. in general population Seborrheic dermatitis prevalence is 3-5%, this high rate can be explain by impairment of immunity in DM that lead to increase (Malassesazia spp) activity which will lead to inflammation and desqumenation [11], This finding correlate with EdidenDV [4] and Abhishek Goyal [9]. Six(6.3%) patients had eczema, three of them had contact dermatitis, two had juvenile planter dermatitis ,one had atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…NEG leads to the formation of advanced glycation end products (AGEs) that are responsible for decreases in both acid solubility and enzymatic digestion of cutaneous collagen [10]. Disorders such as diabetic thick skin and limited joint mobility (LJM) are thought to result directly from accumulation of AGEs [11].…”
Section: Cutaneous Manifestations (Cm) Of Diabetes Mellitus (Dm)mentioning
confidence: 99%